3D printing and additive manufacturing technologies - Kumar, L. Jyothish; Pandey, Pulak M.; Wimpenny, D. I. (Springer, 2019)
This book presents a selection of papers on advanced technologies for 3D printing and additive manufacturing, and demonstrates how these technologies have changed the face of direct, digital technologies for the rapid production of models, prototypes and patterns. Because of their wide range of applications, 3D printing and additive manufacturing technologies have sparked a powerful new industrial revolution in the field of manufacturing. The evolution of 3D printing and additive manufacturing technologies has changed design, engineering and manufacturing processes across such diverse industries as consumer products, aerospace, medical devices and automotive engineering. This book will help designers, R & D personnel, and practicing engineers grasp the latest developments in the field of 3D Printing and Additive Manufacturing.- Resumé vydavatel
Keywords: trojrozměrný tisk; three-dimensional printing; elektronické knihy; sborníky; electronic books; papers of several authors